2018
DOI: 10.1038/s41398-018-0119-5
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal deprivation induces alterations in cognitive and cortical function in adulthood

Abstract: Early life trauma is a risk factor for a number of neuropsychiatric disorders, including schizophrenia (SZ). The current study assessed how an early life traumatic event, maternal deprivation (MD), alters cognition and brain function in rodents. Rats were maternally deprived in the early postnatal period and then recognition memory (RM) was tested in adulthood using the novel object recognition task. The expression of catechol-o-methyl transferase (COMT) and glutamic acid decarboxylase (GAD67) were quantified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 101 publications
(108 reference statements)
1
13
0
1
Order By: Relevance
“…Previous studies have demonstrated the involvement of the mPFC in the regulation of conditioned fear learning (Resstel et al, 2006; Almada et al, 2013; Marek et al, 2018; Spalding, 2018). Although mPFC neurons respond to noise (Bubser and Koch, 1994; Kim et al, 2009; Likhtik et al, 2014), clicks (Mihalick et al, 2001; Martin-Cortecero and Nunez, 2016; Janetsian-Fritz et al, 2018) and pure tones (Sierra-Mercado et al, 2006; Fenton et al, 2014; Likhtik et al, 2014), iso-frequency pure tones such as 3 kHz (Fenton et al, 2014), 4 kHz (Sierra-Mercado et al, 2006), and 8 kHz (Likhtik et al, 2014) have been used as CSs in conditioned fear learning. Since there has been no further study on the frequency response properties of mPFC neurons to pure tones, the pure tone responses of mPFC neurons and whether they change after auditory fear conditioning, as well as the connection between the sound responses of mPFC neurons and any hypothetical emergent discriminative learning, remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the involvement of the mPFC in the regulation of conditioned fear learning (Resstel et al, 2006; Almada et al, 2013; Marek et al, 2018; Spalding, 2018). Although mPFC neurons respond to noise (Bubser and Koch, 1994; Kim et al, 2009; Likhtik et al, 2014), clicks (Mihalick et al, 2001; Martin-Cortecero and Nunez, 2016; Janetsian-Fritz et al, 2018) and pure tones (Sierra-Mercado et al, 2006; Fenton et al, 2014; Likhtik et al, 2014), iso-frequency pure tones such as 3 kHz (Fenton et al, 2014), 4 kHz (Sierra-Mercado et al, 2006), and 8 kHz (Likhtik et al, 2014) have been used as CSs in conditioned fear learning. Since there has been no further study on the frequency response properties of mPFC neurons to pure tones, the pure tone responses of mPFC neurons and whether they change after auditory fear conditioning, as well as the connection between the sound responses of mPFC neurons and any hypothetical emergent discriminative learning, remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the postnatal risk factors, many studies focused on early life stress, such as malnutrition and maternal separation [ 40 , 51 ]. Remarkably, animal models of maternal deprivation have been used to address several behavioral and neurochemical changes in the offspring’s brains.…”
Section: Schizophreniamentioning
confidence: 99%
“…Recent studies have found that animals having undergone mother‐to‐child separation also show impaired recognition memory. The expression of both the Catechol‐O‐methyltransferase (COMT) in the medial prefrontal cortex and temporal cortex, and glutamic acid decarboxylase 67 (GAD67) in the temporal cortex enzyme 67 are reduced (Janetsian‐Fritz et al, 2018). Other studies have shown that chronic use of clozapine can reverse the learning deficit of this rat model rat in the T maze test (Li, Wu, & Li, 2007), and the antipsychotic drug raclopride can reverse prepulse inhibition (PPI) deficiency.…”
Section: Neurodevelopmental Animal Experimental Modelmentioning
confidence: 99%